1991
DOI: 10.1177/074873049100600104
|View full text |Cite
|
Sign up to set email alerts
|

The Visual Input Stage of the Mammalian Circadian Pacemaking System: I. Is There a Clock in the Mammalian Eye?

Abstract: Threads of evidence from recent experimentation in retinal morphology, neurochemistry, electrophysiology, and visual perception point toward rhythmic ocular processes that may be integral components of circadian entrainment in mammals. Components of retinal cell biology (rod outer-segment disk shedding, inner-segment degradation, melatonin and dopamine synthesis, electrophysiological responses) show self-sustaining circadian oscillations whose phase can be controlled by light-dark cycles. A complete phase resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 143 publications
(65 citation statements)
references
References 145 publications
(108 reference statements)
1
63
0
1
Order By: Relevance
“…In nocturnal or crepuscular animals with rod-dominated retinas, rods are likely to be of predominant importance for the circadian system as mediators of dawn and dusk signals (Remé et al, 1991). Experiments with the rd mouse have shown that melatonin synthesis is not abolished by the complete loss of rod photoreceptors, while the circadian expression disappears with the loss of these photoreceptors .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In nocturnal or crepuscular animals with rod-dominated retinas, rods are likely to be of predominant importance for the circadian system as mediators of dawn and dusk signals (Remé et al, 1991). Experiments with the rd mouse have shown that melatonin synthesis is not abolished by the complete loss of rod photoreceptors, while the circadian expression disappears with the loss of these photoreceptors .…”
Section: Discussionmentioning
confidence: 99%
“…Both disc shedding and autophagy follow a circadian rhythm in mammals (LaVail, 1976;Remé et al, 1985). The light history of a given animal (Penn and Williams, 1986), however, defines the amplitude of that rhythm and the overall "sensitivity" of the system to light exposure (Remé et al, 1991). Disk shedding and autophagy not only follow a circadian rhythm but may also be evoked or their amplitude modified by light exposures (Remé et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations